Studies on the cytotoxicity of compounds from Carica papaya Linn. extracts - Orejola, Joanna J.
Carica papaya Linn. is a well-documented medicinal plant. The leaves and seeds are studied for biological activity, while the fruits are most likely used for food and cosmetic purposes. This study aimed to determine the cytotoxic activity of various parts of the plant and identification of the group of compounds responsible for this activity. The crude chloroform and aqueous extracts of the leaves, fruits and seeds were tested for cytotoxic activity using (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. Only the crude leaf chloroform extract showed cytotoxic activity against the cell lines Human Breast Adenocarcinoma, MCF7 (IC50 = 45.54 μg/mL), Human colorectal Adenocarcinoma, MCF7 (IC50 = 33.72 μg/mL), and Human Ovarian Adenocarcinoma SKOV3 (IC50 = 20.21 μg/mL). The crude chloroform extracts of papaya leaves were fractionated through column chromatography, using an isocratic gradient of 4:4:1 Hexane-Ethyl Acetate-Methanol solvent system on silica gel. Each fractions collected were subjected to Thin Layer Chromatography (TLC). The fractions with similar TLC profile were pooled together. Fractionation was done in two batches. For the first batch of pooled fractions, 4 out of 7 showed mild cytotoxic activity against MCF7 with IC50 values of 68.19 μg/mL, 48.83 μg/mL, 59.83 μg/mL, and 48.77 μg/mL, while 3 pooled fractions exhibited mild cytotoxicity against HT29 with IC50 values of 42.29 μg/mL, 90.78 μg/mL, and 76.39 μg/mL. For the second batch of pooled fractions, only one showed cytotoxicity against SKOV3 (IC50 = 75.26 μg/mL). Phytochemical screening and TLC revealed that tannins, polyphenols, reducing substances, alkaloids, glycosides and terpenes are the possible plant constituents responsible for the cytotoxicity of Carica papaya against the cell lines MCF7, HT29, and SKOV3. Carica papaya leaves have potential anticancer property and this could be further confirmed through isolation and purification of the cytotoxic agents followed by testing the cytotoxic activity against a larger panel of cancer cell lines. The fruits, which are commonly used as main ingredient in food and cosmetics, are deemed to be safe for consumption since they did not show cytotoxic activity. Further research is needed to evaluate the cytotoxic activity of the seeds.
Thesis (Master of Science in Biochemistry)--University of the Philippines Manila, 2010.
Available to the general public.
Keywords: Papaya -- Therapeutic use; Carica papaya